Diseño de un manual de procesos a partir de la identificación del estado administrativo-operativo del cuerpo de bomberos de Latacunga - Auz Carvajal, Victor Alfonso (2015)
This thesis project is developed in the Latacunga Fire Department, an autonomous institution and social service, whose mission is to protect life, property and the environment through timely and effective action in the fight against fire, and rescue. This paper has been developed as a management tool that can be used in all levels of decision and attention provided by the institution, in order to strengthen the administrative system and operation. The main objective of this project lies in describing the institutional activities, which are involved in every area of the Latacunga Fire Department, with the purpose of standardizing the methods of work, through logical sequential steps to provide better service, thus achieving an improvement in organizational culture. That is because it is proposed to design a process manual, which will serve as an element of consultation, orientation and training for staff.